Coverage and Handover Analysis of Ultra-Dense Millimeter-Wave Networks With Control and User Plane Separation Architecture - Bin Yang (IEEE Access, 2018)
The control and user plane separation (CUPS) architecture becomes more appealing for higher mobility profiles with the densification of networks. Compared with the conventional architecture where the control plane and the user plane are closely coupled, CUPS architecture is envisioned to provide enhancement for networks in a flexible way, e.g., reducing latency on application service, while not affecting the functionality of the existing base stations (BSs). In this paper, we compare the performance of ultra-dense millimeter-wave networks with the CUPS architecture and the conventional architecture. An analytical framework is proposed to study the coverage probability, which takes the propagation characteristic of millimeter wave into consideration. The proposed framework is then simplified in an ultra-dense scenario, where two optimization problems are formulated to achieve the minimum handover cost subject to a certain coverage probability requirement. Numerical results show that the CUPS architecture outperforms the conventional architecture in terms of the coverage probability as well as the handover cost. Moreover, new insights are obtained on the deployment of ultra-dense millimeter-wave networks. To be specific, the handover cost of networks with the conventional architecture can be effectively reduced by adding more macrocell BSs, while it is beneficial to add smaller cell BSs into networks with the CUPS architecture.